1986
DOI: 10.1254/jjp.41.7
|View full text |Cite
|
Sign up to set email alerts
|

Depression of Drug-Induced Tremor by a New Isoxazol Derivative in Mice

Abstract: Abstract-The effects of a newly synthesized compound, MLV-208, on drug induced tremor were investigated in mice. The study involved a power spectral analysis of the random current induced by movement of a magnet attached to the mouse on a wire coil. To induce tremor, tremorine and harmaline were subcu taneously injected.The power spectral density function defined the frequency composition of the tremor, and its severity was determined quantitatively in terms of the mean square value of the data in any frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…The results were quite similar to those described previously Shinozaki & Hirate, 1986). Gross observations of the test groups receiving MLV-6976, revealed that neither the tremor nor the other effects induced by tremorine seemed to be reduced.…”
Section: Antagonism Of Drug-induced Tremor In Micesupporting
confidence: 91%
See 3 more Smart Citations
“…The results were quite similar to those described previously Shinozaki & Hirate, 1986). Gross observations of the test groups receiving MLV-6976, revealed that neither the tremor nor the other effects induced by tremorine seemed to be reduced.…”
Section: Antagonism Of Drug-induced Tremor In Micesupporting
confidence: 91%
“…Mice receiving tremorine at a subcutaneous dose of 70 mg kg' demonstrated severe tremor, diminished normal locomotor activity, and profuse salivation, lachrymation and diarrhoea. The results were quite similar to those described previously Shinozaki & Hirate, 1986). Gross observations of the test groups receiving MLV-6976, revealed that neither the tremor nor the other effects induced by tremorine seemed to be reduced.…”
Section: Antagonism Of Drug-induced Tremor In Micesupporting
confidence: 91%
See 2 more Smart Citations
“…Besides, isoxazole, as a very important five‐membered heterocyclic compound containing nitrogen and oxygen, is widely used in organic synthesis and medical fields because of its good biological activity and pharmacological activity. Previous works have demonstrated that the compounds bearing isoxazole group had a series of pharmacological and biological activities such as anti‐HIV, [20] anti‐tumor, [21,22] antioxidant, [23] antimicrobial, [24] anti‐TB, [25,26] anti‐depression, [27,28] anti‐fungal, [29,30] DNA elimination, [31–33] anti‐cancer, [34,35] and so on. Besides, lots of its derivatives can be used in pesticide field with high efficiency, unique mechanism and non‐pollution [36] .…”
Section: Introductionmentioning
confidence: 99%